Vitamin E and Mortality in Male Smokers of the ATBC Study: Implications for Nutritional Recommendations - Hemilä, Harri (Frontiers in Nutrition, 2020)
The Dietary Reference Intakes (DRI)-monograph (USA/Canada) states that the estimated average requirement (EAR) of vitamin E for men and women of any age is 12 mg/day. The EAR value is based on in vitro hemolysis in young males; a surrogate endpoint without any direct validity. The EAR is then extrapolated to females and older males. The validity of the EAR level is therefore questionable. Total mortality is an outcome of direct clinical relevance. Investigating the effect of long-term dietary vitamin E intake level on mortality in a randomized trial is, however, not feasible. Nevertheless, the effect of dietary vitamin E intake can be investigated indirectly from the effects of a fixed-level vitamin E supplement administered to participants on variable levels of dietary vitamin E intake. If vitamin E intake below the EAR is harmful, then vitamin E supplement should be beneficial to those people who have dietary vitamin E intake level below the EAR. The purpose of this study was to analyze the association between dietary vitamin E intake and the effect of 25 mg/day of vitamin E supplement on total mortality in Finnish male smokers aged 50–69 years in the Alpha-Tocopherol-Beta-Carotene (ATBC) Study. The effect of vitamin E supplement was estimated by Cox regression. Among participants who had dietary vitamin C intake of 90 mg/day and above, vitamin E supplement increased mortality by 19% (p = 0.006) in those aged 50–62 years, but decreased mortality by 41% (p = 0.0003) in those aged 66–69 years. No association between vitamin E supplement effect and dietary vitamin E intake was found in these two groups, nor in participants who had dietary vitamin C intake less than 90 mg/day. There is no evidence in any of the analyzed subgroups that there is a difference in the effect of the 25 mg/day vitamin E supplement on males on dietary vitamin E intakes below vs. above the EAR of 12 mg/day. This analysis of the ATBC Study found no support for the ‘estimated average requirement' level of 12 mg/day of vitamin E for older males. Trial registration:ClinicalTrials.gov, identifier: NCT00342992.